Transcriptomic Responses of Four Pelagophytes to Nutrient (N, P) and Light Stress - Kang, Yoonja; Harke, Matthew J.; Berry, Dianna L.; Collier, Jackie L.; Wilhelm, Steven W.; Dyhrman, Sonya T.; Gobler, Christopher J. (Frontiers in Marine Science, 2021)
Pelagophytes are abundant picophytoplankton within open ocean ecosystems and the causative algae of harmful brown tide blooms in estuaries. The physiological capabilities facilitating the ecological success of pelagophytes in these diverse ecosystems remains poorly understood. Here, we investigated the transcriptional response of two coastal pelagophytes (Aureococcus anophagefferens and Aureoumbra lagunensis) and two open ocean pelagophytes (Pelagococcus subviridis and Pelagomonas calceolata) to conditions commonly found within the marine ecosystems where they thrive: low concentrations of nitrogen (N), phosphorus (P), or light. OrthoMCL was used to generate a total of 62,653 orthologous groups (OGs) with only a small fraction of these OGs (2,776 or 4.4%) being commonly shared among all four pelagophytes. Of the commonly shared OGs, 8% were significantly differentially abundant under low N, P, or light with the majority associated with energy and lipid metabolism. Distinct responses among pelagophytes included increased abundance of transcripts encoding phosphate transporters (Aureococcus) and transcripts encoding a pyrophosphatase (Aureococcus and Pelagomonas) under low P, the expression of a suite of organic nitrogen-degrading enzymes under low N (Aureoumbra and Pelagomonas), increased abundance of transcripts encoding flavodoxins relative to ferredoxins (Pelagomonas) and transcripts encoding lysophospholipase (Pelagococcus) under low light, and both increases and decreases in abundance of transcripts encoding selenoproteins in all pelagophytes except Pelagococcus. Collectively, this study provides new information on the expressed gene compliment of these poorly characterized taxa and demonstrates that these pelagophytes possess a combination of shared and unique physiological features that likely facilitate their adaptation to distinct environmental conditions.